Sociometric status of participants involved in school bullying - Zequinão, Marcela Almeida (2020)
The situation of social vulnerability hinders the integration processes and thus can foster problems in interpersonal interactions in school. This study aimed to analyze the sociometric status and its relationships with sex, age and profiles of bullying participation in children and adolescents in situations of social vulnerability. A total of 409 students between the third and seventh grades of two public elementary schools in Florianópolis-SC participated in this study. The positive status was higher for boys (M = 11.07; SD = 8.52) and adolescents (M = 11.46; SD = 8.19) compared to girls (M = 8.55; SD = 5.60) and children (M = 8.83; SD = 6.56). The aggressors’ positive status was higher, with significant difference, compared to victims and non participants of bullying (p = 0.008). In the context of bullying, aggressors’ high status can collaborate to their use of violence in conflict resolution or to gain peer popularity.